2010
DOI: 10.1021/jm901823u
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Photocytotoxicity of Boron Dipyrromethene Derivatives for Photodynamic Therapy

Abstract: To understand the effects of substitution patterns on photosensitizing the ability of boron dipyrromethene (BODIPY), two structural variations that either investigate the effectiveness of various iodinated derivatives to maximize the "heavy atom effect" or focus on the effect of extended conjugation at the 4-pyrrolic position to red-shift their activation wavelengths were investigated. Compounds with conjugation at the 4-pyrrolic position were less photocytotoxic than the parent unconjugated compound, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
217
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 341 publications
(226 citation statements)
references
References 24 publications
5
217
0
4
Order By: Relevance
“…For each liposomal preparation, the experiment was performed at least three times. Acquisition of images was made pre-and post-photodynamic therapy and was compared and graded according to the criteria described elsewhere with minor modification [3,34]. Briefly, depending on the degree of the vascular occlusion of CAM after PDT, the response was graded according to the degree of vascular closure and/or destruction representing the level of treatment (Table 2).…”
Section: Intravenous Injection Of Ce6 In Tels-liposomes and Image Acqmentioning
confidence: 99%
“…For each liposomal preparation, the experiment was performed at least three times. Acquisition of images was made pre-and post-photodynamic therapy and was compared and graded according to the criteria described elsewhere with minor modification [3,34]. Briefly, depending on the degree of the vascular occlusion of CAM after PDT, the response was graded according to the degree of vascular closure and/or destruction representing the level of treatment (Table 2).…”
Section: Intravenous Injection Of Ce6 In Tels-liposomes and Image Acqmentioning
confidence: 99%
“…The CAM model is often used as a model for PDT-induced angioocclusion [23,34]. We observed that Visudyne ® -PDT, applied at EDD11, induced an efficient closure of the vasculature ( Fig.…”
Section: Morphological and Molecular Response In The Cam After Pdtmentioning
confidence: 83%
“…Moreover, the BODIPY PSs with heavy atoms, such as I, Br, Se, S etc. may offer increased dark toxicity, and altered biodistribution as well as pharmacokinetics [39,40].…”
Section: Introductionmentioning
confidence: 99%